Lessons learned : critical information infrastructure protection : how to protect critical information infrastructure - Viira, Toomas (IT Governance Publishing, 2018)
""I loved the quotes at the beginning of each chapter - very interesting and thought-provoking. I also enjoyed the author's style and his technical expertise shone through.""Christopher Wright, Wright CandA Consulting LtdProtecting critical information infrastructure (CII) is not an easy process. Risks need to be minimised and systems adequately protected. It is an endless balancing act, where one side is constantly on the defensive and the other on the offensive. Lessons Learned: Critical Information Infrastructure Protection aims to help you be as successful as possible in protecting your CI.
Keywords: Data protection.; Information resources management.; Information superhighway.; elektronické knihy; electronic books